When Criminal Coping is Likely: an Examination of Conditioning Effects in General Strain Theory - Thaxton, Sherod (Journal of quantitative criminology, 2018)
This paper addresses a central problem in general strain theory (GST): the mixed results regarding those factors said to condition the effect of strains on crime. We test Agnew's (Deviant Behav 34(8):653-670, 2013) assertion that a criminal response to strain is likely only when individuals score high on several factors that increase the propensity for criminal coping or possess markers that indicate a strong propensity for criminal coping.